2023
DOI: 10.1186/s12967-023-04206-3
|View full text |Cite
|
Sign up to set email alerts
|

Inhalable CAR-T cell-derived exosomes as paclitaxel carriers for treating lung cancer

Abstract: Background Non-small cell lung cancer (NSCLC) is a worldwide health threat with high annual morbidity and mortality. Chemotherapeutic drugs such as paclitaxel (PTX) have been widely applied clinically. However, systemic toxicity due to the non-specific circulation of PTX often leads to multi-organ damage, including to the liver and kidney. Thus, it is necessary to develop a novel strategy to enhance the targeted antitumor effects of PTX. Methods He… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 60 publications
(58 reference statements)
0
10
0
Order By: Relevance
“…Paclitaxel was encapsulated in these CAR-Exos (PTX@CAR-Exos) and administered to lung cancer mouse models through inhalation. The results showed that inhaled PTX@CAR-Exos accumulated within the tumor area and signi cantly reduced tumor size, extended survival time, and exhibited lower toxicity [25][26][27][28]. Rezakhani et al's study used various EVs loaded with doxorubicin and paclitaxel to treat different types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Paclitaxel was encapsulated in these CAR-Exos (PTX@CAR-Exos) and administered to lung cancer mouse models through inhalation. The results showed that inhaled PTX@CAR-Exos accumulated within the tumor area and signi cantly reduced tumor size, extended survival time, and exhibited lower toxicity [25][26][27][28]. Rezakhani et al's study used various EVs loaded with doxorubicin and paclitaxel to treat different types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes have inherent biochemical characteristics that contribute to their extensive application in drug-delivery systems (figure 3). Exosomes can be loaded with different cargoes, including proteins, genetic substances (miRNA and siRNA), and drug molecules (doxorubicin, paclitaxel, methotrexate, and curcumin), using physical, chemical, or biological methods [115][116][117][118][119][120].…”
Section: Therapeutic Modalities Involving Delivery Of Cargoes Through...mentioning
confidence: 99%
“…151 In cancer treatment, CAR T-cell-derived exosomes are an effective solution. 152,153 Modified exosomes, artificial exosomes, and chimeric exosomes are frontiers of exosomesbased translational medicine, and these types of exosomes show effective antitumor activity. 154−156 Engineered exosomes developed after modifications in surface and inner cargo level is effective on anticancer activity.…”
Section: Application Of Modified Exosomes In Cancermentioning
confidence: 99%
“…This method is limited in life-threatening toxicity, but the most exciting fact is CAR T-cell-derived exosomes are less toxic compared to CAR-T therapy . In cancer treatment, CAR T-cell-derived exosomes are an effective solution. , Modified exosomes, artificial exosomes, and chimeric exosomes are frontiers of exosomes-based translational medicine, and these types of exosomes show effective antitumor activity. Engineered exosomes developed after modifications in surface and inner cargo level is effective on anticancer activity. Modified exosomes have now become the leading approach in exosomes-based cancer therapy.…”
Section: Application Of Modified Exosomes In Cancermentioning
confidence: 99%